Geopolitics and War within a 280 Characters Limit: A Positive and Normative Analysis of Elon Musk’s “peace plan” for Ukraine - Sabina RUSU (Perspective Politice, 2023)
The subject of the current conference paper concerns Elon Musk’s “peace plan” for ending the war Russia started on February 24th 2022 against the independent and sovereign Ukrainian state, that he tweeted in October 2022, so seven months into the military confrontations between the two sides. Starting with the intuitive assumptions that combat is costly for each side, and that “every war must end” (Ikle, 1971) – so there will be a form of war termination also for Russia’s invasion of Ukraine – the research question that I will address is whether Musk’s simplistic forty-two words proposal could represent an actual peace settlement or at least a genuine basis for peace negotiations between Kyiv and Moscow. In order to address the issue, I start by presenting Musk’s “peace plan”, then I argue that the specific proposals: (i) do not lay the foundations for a durable and stable peace in Europe, on the contrary, they are a form of appeasement towards Russia, an aggressor state; (ii) represent mostly Putin’s claims for starting the war in the first place – they are not neutral, but come very close to Moscow’s position and demands, while also the language is overtly favourable towards Russia; (iii) would be impossible to implement without recognizing/ legitimizing Russia’s policy in the temporary occupied territories of Ukraine. The analysis contributes to a better understanding of the reasons for war continuation for the time being, despite limitations stemming from the fast pace of the battlefield events unfolding (that change the negotiations power between the sides) and also from the lack of information on if and how negotiations are held during wartime and what are the real reasons why the settlement process is delayed.